2003
DOI: 10.1111/j.1572-0241.2003.07708.x
|View full text |Cite
|
Sign up to set email alerts
|

High rates of recurrence and of transient reinfections of Helicobacter pylori in a population with high prevalence of infection

Abstract: In our population, recurrence rate is high in adults and transient reinfection is common. In several cases, reinfection occurred by multiple strains, which suggests that soon after eradication, patients are exposed to multiple sources of reinfection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 33 publications
3
22
0
1
Order By: Relevance
“…3 for the developed countries [4,6,7,[10][11][12][13], and in Fig. 4 for the developing countries [16,17,19,20]. The nested meta-analysis revealed an annual recurrence rate of 1.45% in the developed and 12% in the developing countries.…”
Section: Resultsmentioning
confidence: 96%
“…3 for the developed countries [4,6,7,[10][11][12][13], and in Fig. 4 for the developing countries [16,17,19,20]. The nested meta-analysis revealed an annual recurrence rate of 1.45% in the developed and 12% in the developing countries.…”
Section: Resultsmentioning
confidence: 96%
“…In both experimental (10) and accidental (12,13) exposures of humans to the organism, H. pylori detection and associated inflammation were followed by spontaneous clearance within 14 days in a subset of subjects; in others the infections persisted. Epidemiological studies have also shown evidence of transient H. pylori infections in young children (17) and patients previously cured of H. pylori (9). In addition to humans, transient infections have also been reported in previously cured macaques (23).…”
Section: Discussionmentioning
confidence: 93%
“…In the developing world, the reinfection rates have ranged widely, from 1.1% at 2 years in China, to 73% at 8 months in studies from Peru. [16][17][18][19][20][21][22] Intermediate rates of reinfection are found in the Mediterranean region and Japan, ranging from 1.5% to 16.7%. 15,[28][29][30][31][32][33][34] It is sometimes difficult to distinguish between reinfection, defined as the complete eradication of an H. pylori infection followed by the introduction of a new H. pylori infection and recrudescence, defined as the apparent clearance of an H. pylori infection due to suppression but not eradication of the organism, followed by a positive test for H. pylori.…”
Section: Discussionmentioning
confidence: 99%
“…In developed countries, annual reinfection rates range from 0.36% in Australia to 5.7% in Italy [8][9][10][11][12][13][14][15] and in developing countries from 1.1% in China to 73% in Peru. [16][17][18][19][20][21][22] However, information regarding risk factors for reinfection is scanty.…”
Section: Introductionmentioning
confidence: 99%